'Open source has won and lost the war': Legitimising commercial–communal hybridisation in a FOSS project. (May 2021) - O'Neil, Mathieu; Muselli, Laure; Raissi, Mahin; Zacchiroli, Stefano
Information technology (IT) firms are paying developers in Free and Open Source Software (FOSS) projects, leading to the emergence of hybrid forms of work. In order to understand how the firm–project hybridisation process occurs, we present the results of an online survey of participants in the Debian project, as well as interviews with Debian Developers. We find that the intermingling of the commercial logic of the firm and the communal logic of the project requires rhetorical legitimation. We analyse the discourses used to legitimise firm–project cooperation as well as the organisational mechanisms which facilitate this cooperation. A first phase of legitimation, based on firm adoption of open licenses and developer self-fulfilment, aims to erase the commercial/communal divide. A second more recent phase seeks to professionalise work relations inside the project and, in doing so, challenges the social order which restricts participation in FOSS. Ultimately, hybridisation raises the question of the fair distribution of the profits firms derive from FOSS.